Some biochemical properties and the classification of a range of bacterial haloalkane dehalogenases - Damborsky, J; Nyandoroh, M G; Nĕmec, M; Holoubek, I; Bull, A T; Hardman, D J (Biotechnology and applied biochemistry, 1997)
Multivariate analyses and experimental data have been used to evaluate the relationships between eight bacterial hydrolytic haloalkane dehalogenases. The results indicate that seven of the dehalogenases investigated can confidently be placed into two Classes [sensu Slater, Bull and Hardman (1995) Biodegradation 6, 181-189] according to their substrate profiles. The remaining enzyme, isolated from Rhodococcus erythropolis CP9, appears to represent a third Class of haloalkane dehalogenases.
Keywords: Molecular Sequence Data; Hydrolases; elektroforéza v polyakrylamidovém gelu; Blotting, Western; Electrophoresis, Polyacrylamide Gel; sekvence aminokyselin; molekulární sekvence - údaje; hydrolasy; sekvenční homologie aminokyselin; Amino Acid Sequence; Bacteria; Sequence Homology, Amino Acid; western blotting